CORNELL NOTE-TAKING: EFFECTIVE WAY TO ACTIVATE STUDENTS’ AUTONOMOUS LEARNING - Luh Eka Susanti (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
Memory is fragile, as it is easy to be forgotten. People who take notes typically retain more information which has a positive effect on learning (Titsworth in Borr et al., 2012). Note-taking acts as a tool to provide students for identifying and understanding the most important aspects of what they are learning (Borr et al., 2012). Cornell note-taking was selected as a short condensation of a source material that is generated by writing them down while simultaneously listening, studying, or observing. It has some sections which it can be filled with the questions or keywords, elaboration, and summary. This study was conducted for hospitality students in International Business and Tourism Institute, in particular Diploma III Hotel Operation when they were learning about Business English for Hotel and Tourism. The result could be seen that note-taking students got higher score and could easily recall information both in written and spoken test.